Analisis Kritis terhadap Pengajaran Bab Nikah dalam Kitab Fathul Wahab di Pondok Pesantren Raudatul Muhibbin Al-Mustainiyah Surakarta : Critical Analysis of the Teaching of the Marriage Chapter in the Book of Fathul Wahab at the Raudatul Muhibbin Al-Mustainiyah Islamic Boarding School, Surakarta - Syifa Alya Nabilah; Akmal Khoirul Huda; M. Fahmy (DIRASAH: Jurnal Kajian Islam, 2026)
This study aims to critically analyze the methods, approaches, and relevance of teaching the Nikah (marriage) chapter from Fathul Wahhab at Pondok Pesantren Raudhatul Muhibbin AlMustainiyah, Surakarta. The research focuses on how students’ understanding of marriage concepts within the Shafi‘i school of Islamic jurisprudence is shaped through the traditional kitab kuning (classical Islamic text) learning system, while also responding to contemporary social and legal dynamics. This qualitative research employs a descriptive-analytical method. Data were collected through observation, interviews with teachers and students, and analysis of the instructional materials. The findings reveal that the teaching process remains centered on bandongan and sorogan methods but has been contextualized with modern phenomena such as marriage registration, the role of guardians (wali), and the issue of early marriage. The critical analysis indicates that this educational approach not only preserves the classical values of Shafi‘Analysis i jurisprudence but also creates opportunities for integrating Islamic legal thought with social realities. Consequently, the teaching of Fathul Wahhab in this pesantren represents a harmonious synthesis between classical Islamic scholarship and the contemporary needs of Islamic law.